The Effects of Climate Change on Mental Health - Walinski, Annika; Sander, Julia; Gerlinger, Gabriel; Clemens, Vera; Meyer-Lindenberg, Andreas; Heinz, Andreas (Deutsches Ärzteblatt international, 2023)
All over the world, climate change is exerting negative and complex effects on human living conditions and health. In this narrative review, we summarize the current global evidence regarding the effects of climate change on mental health. A systematic literature search concerning the direct effects of acute extreme weather events (floods, storms, fires) and chronic stresses (heat, drought) due to climate change, as well as the indirect effects of climate change (food insecurity, migration), on the diagnoses of mental disorders, psychological distress, and psychiatric emergency admissions was carried out in PubMed and PsychInfo, and supplemented by expert selection. 1017 studies were identified, and 128 were included. The heterogeneity of study methods does not permit any overall estimate of effect strength. The available evidence shows that traumatic experiences due to extreme weather events increase the risk of affective and anxiety disorders, especially the risk of post-traumatic stress disorder. Heat significantly increases the morbidity and mortality attributable to mental illness, as well as the frequency of psychiatric emergencies. Persistent stressors such as drought, food insecurity, and migration owing to climate change can also be major risk factors for mental illness. The consequences of climate change are stress factors for mental health. Therefore, as global warming progresses, an increasing incidence and prevalence of mental illness is to be expected. Vulnerable groups, such as the (already) mentally ill, children, and adolescents, need to be protected. At the same time, there is a need for further systematic research on the mechanisms of action and effects of climate change on mental function.